From assistive to enhancing technology: should the treatment-enhancement distinction apply to future assistive and augmenting technologies?. Issue 4 (14th October 2017) - Minerva, Francesca; Giubilini, Alberto
Abstract : The treatment-enhancement distinction is often used to delineate acceptable and unacceptable medical interventions. It is likely that future assistive and augmenting technologies will also soon develop to a level that they might be considered to provide users, in particular those with disabilities, with abilities that go beyond natural human limits, and become in effect an enhancing technology. In this paper, we describe how this process might take place, and discuss the moral implications of such developments. We argue that such developments are morally acceptable and indeed desirable.